Upaya Meningkatkan Hasil Belajar Siswa Kelas IV Melalui Penggunaan Media Visual di SDN 3 Sukarasa - Imas Nopi (Journal on Education, 2020)
This research was conducted at SDN 03 Sukarasa on the material on the mind map material from nonfiction stories. This study uses a classroom action research method which is divided into 3 learning cycles. The research aims to improve student learning outcomes through learning using visual media. This study was applied to 8 samples with the duration of the study consisting of 6 meetings. Based on the value analysis shows that there is an increase in student learning outcomes both from cycle I, cycle II, and cycle III. This is because in cycle II learning activities by adding learning media in the form of visual media have a good effect on student learning outcomes, this is evidenced by the increase in the mean value of students. Likewise with the addition of learning media in the form of pictures and learning videos and discussions, question and answer with students in learning cycle III has had a very good influence on student learning outcomes, understanding of the subject matter being taught and the activeness of students and providing a different atmosphere in activities learning.